Unveiling cultural values and pedagogical insights through the terminologies of the Sasak Kepaten tradition - Saadilah Husni; Mahsun Mahsun; Burhanudin Burhanudin; Aswandikari Aswandikari; Saharudin Saharudin (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
This study explores the ritual language system in the kepaten tradition of the Sasak community from the perspective of anthropological linguistics. It aims to identify the linguistic forms, cultural meanings, and value systems embedded in death ritual expressions. Language in this context is viewed not merely as a communicative tool but as a symbolic mechanism that structures social, spiritual, and moral behavior. Employing a qualitative–descriptive method through observation, interviews, and documentation, the research collected ritual lexicons analyzed using HBB, HBS, and HBSP techniques to construct taxonomies and semantic domains across three main stages: nyiepan ‘pre-burial’, nguburan ‘burial’, and suwahan ‘post-burial’. The findings reveal that each linguistic form conveys not only lexical meaning but also a triadic value system connecting human–human, human–nature, and human–God relationships. These values form the foundation of what this study terms language as moral ecology—a linguistic system that regulates ethical conduct and sustains communal harmony. From a pedagogical standpoint, the kepaten lexicons provide culturally grounded learning materials that can nurture solidarity, spirituality, and ecological care in character education. Overall, the study enriches anthropological linguistics by positioning ritual discourse as both a moral–ecological practice and a model for heritage-based pedagogy rooted in Sasak cultural wisdom.   Penelitian ini mengkaji sistem bahasa ritual dalam tradisi kepaten masyarakat Sasak melalui perspektif linguistik antropologis. Tujuannya adalah untuk mengidentifikasi bentuk-bentuk lingual, makna budaya, dan sistem nilai yang terkandung dalam tuturan ritual kematian. Bahasa dalam konteks ini tidak dipandang semata sebagai alat komunikasi, melainkan sebagai mekanisme simbolik yang menstrukturkan perilaku sosial, spiritual, dan moral masyarakat. Dengan menggunakan metode kualitatif-deskriptif melalui observasi, wawancara, dan dokumentasi, penelitian ini menghimpun leksikon ritual yang dianalisis menggunakan teknik HBB, HBS, dan HBSP untuk membangun taksonomi dan domain semantik pada tiga tahap utama: nyiepan ‘pra-pemakaman’, nguburan ‘pemakaman’, dan suwahan ‘pasca-pemakaman’. Temuan penelitian menunjukkan bahwa setiap bentuk lingual tidak hanya memuat makna leksikal, tetapi juga merepresentasikan sistem nilai triadik yang menghubungkan relasi manusia dengan sesama, manusia dengan alam, dan manusia dengan Tuhan. Nilai-nilai ini menjadi dasar dari konsep bahasa sebagai ekologi moral (language as moral ecology), yaitu sistem linguistik yang menata perilaku etis dan menjaga keharmonisan sosial. Dari sudut pandang pedagogis, leksikon kepaten dapat dijadikan sumber pembelajaran berbasis budaya yang menumbuhkan solidaritas, religiusitas, dan kepedulian ekologis dalam pendidikan karakter. Secara keseluruhan, penelitian ini memperkaya kajian linguistik antropologis dengan menempatkan wacana ritual sebagai praktik moral-ekologis sekaligus model pedagogi berbasis kearifan lokal masyarakat Sasak.